ONSET DAN INTENSITAS ESTRUS KAMBING PADA UMUR YANG BERBEDA - Mohammad Ismail (Universitas Tadulako, 2009)
An experiment was conducted at the research station of animal husbandry departement, Agricultural Faculty, University of Tadulako Palu. This experiment was carried out from April to March 2008. The objective of the study was to determine the effect of various ages of female local goats on the onset and intensity of estrus. 18 non pregnant local female goats and 3 males as teaser to detect estrus were used in this experiment. Experiment consisted of two stages; preparation period and observation period. At the first stages the animals were adaptated to the experimental condition, such as feeding concentrate and injection of PGF 2α to syncronize estrus. The estrus syncronization was done by applying twice injections of PGF 2α at day 1 and day 12. The observation period for detection of the estrus onset was done by observing the time interval between injection of PGF 2α and the first estrus onset. This parameter was expressed in hour unit. Observation of estrus intensity was done by detecting level of estrus symptom appeared to every single female goat. The symptom was characterised by different behavior of the goat females at the time of estrus and changes of physical reproductive organs. The results of analysis indicated that different ages significanly affected (P<0.01) the estrus onset and intensity of the animals. The estrus onset of the local goat after estrus syncronization took place at hour 70.06 to 138.42. The onset of estrus was earlier for animals which already gave birth more than once. The animals which had never given birth were the last ones which showed the estrus. The estrus intensity was evident in the animal given birth more that once, whereas for those animals which only experienced giving birth once the intensity was less evident.